A Work study on golden cane furniture manufacturing corporation - Arabit, Ma. Abigail A. (College of Engineering, 1992)
Golden Cane Furniture Manufacturing Corporation is an export-oriented company dedicated to the manufacture of quality furniture. Its main office is found #33 Kalayaan Avenue, Quezon City and its production plant is found in #752 Quirino Highway, Novaliches, Quezon City. Its main operations of production are framing, metal preparation, weaving, sanding and varnishing. The study team observed the company's operations and documented the existing system, the existing layout, operations (Framing and Metal Preparation), and systems and procedures. There were no standard times available for the operations. There are no cleary defined work area for each worker. The company also lack tools and equipment and safety gears such as masks and gloves that will protect the worker from the hazards of production. The production plant is not also well ventilated. There are only a few exhaust fans found in sections where these fans are needed the most. The study team carefully analyzed the existing system and applied work study techniques to improve the system. A time study was conducted and standard times were determined for different operations. A proposed layout is presented in this study in order to improve production efficiency. Recommendations were made regarding fire prevention, occupational health and safety, good housekeeping, lighting and ventilation of the production plant.